1977
DOI: 10.1146/annurev.me.28.020177.000551
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hyperparathyroidism

Abstract: States of hypersecretion of PTH may occur primarily, or in response to other physiologic abnormalities. Primary hyperparathyroidism must be considered in the differential diagnosis of hypercalcemia, nephrolithiasis, metabolic bone disease, and pancreatitis and peptic-ulcer disease. The clinical manifestations of this disease have become more subtle with improved detection. The serum calcium level is almost always elevated, and when it it accompanied by relatively high serum PTH levels or increased urinary cAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…This concept of selective response to calcium supplementation was noted in a study by Resnick et al' l5 Although neither randomized nor placebo controlled, the study indicated that hypertensive patients who were most likely to respond to orally administered calcium supplementation are those with low serum ionized calcium levels and low plasma renin activity. To confuse matters, however, other studies have suggested that 1) a direct relationship exists between serum calcium concentration and blood pressure," 6 "" 8 2) hypercalcemic states," 9 including hyperparafhyroidism, 120 have been associated with hypertension, and 3) induced hypercalcemia raises blood pressure in normotensive subjects. 121 In addition to the epidemiological and clinical data, a few studies have assessed the effects of supplementary dietary calcium on blood pressure in experimental animals.…”
Section: Calcium Magnesium and Trace Elements Dietary Calciummentioning
confidence: 99%
“…This concept of selective response to calcium supplementation was noted in a study by Resnick et al' l5 Although neither randomized nor placebo controlled, the study indicated that hypertensive patients who were most likely to respond to orally administered calcium supplementation are those with low serum ionized calcium levels and low plasma renin activity. To confuse matters, however, other studies have suggested that 1) a direct relationship exists between serum calcium concentration and blood pressure," 6 "" 8 2) hypercalcemic states," 9 including hyperparafhyroidism, 120 have been associated with hypertension, and 3) induced hypercalcemia raises blood pressure in normotensive subjects. 121 In addition to the epidemiological and clinical data, a few studies have assessed the effects of supplementary dietary calcium on blood pressure in experimental animals.…”
Section: Calcium Magnesium and Trace Elements Dietary Calciummentioning
confidence: 99%